First measurement of plasma stagnation radiation in a hohlraum in the Shenguang-III prototype. (13th June 2017) - Ren, Kuan; Liu, Shenye; Xie, Xufei; Du, Huabing; Hou, Lifei; Jing, Longfei; Yang, Dong; Zhao, Yang; Yan, Ji; Yang, Zhiwen; Li, Zhichao; Dong, Jianjun; et al.
Abstract: The measurement of plasma stagnation radiation in a hohlraum is of key importance when exploring the influence of plasma stagnation on hohlraum drive symmetry in indirectly driven inertial confinement fusion experiments. In two typical hohlraum experiments conducted on the Shenguang-III prototype laser facility, the x-ray flux and radiation temperature from a plasma stagnation area 0.2 mm in diameter inside the hohlraum were measured for the first time through the hohlraum laser entrance hole (LEH) using a time and space-resolving flux detector (SRFD). The different flux intensities and radiation temperatures of the plasma stagnation area in the LEH measured using the SRFD were compared with the results detected for the entire LEH using flat-response x-ray detectors. The stagnation area radiation detected using the SRFD was found to be transient and 8.57% lower than that of the entire LEH, which is obviously higher than the tolerable drive asymmetry of an implosion. This important improvement in x-ray radiation measurement of plasma stagnation will further the quantitative understanding of the drive symmetry inside the hohlraum and conduct a strict adjustment for that.